Fatal occupational injuries among non‐governmental employees in Malaysia1. Issue 1 (27th April 2012) - Abas, Adinegara Bin Lutfi; Mohd Said, Datuk Abd. Razzak B.; Aziz Mohammed, Mohammed Azman B.; Sathiakumar, Nalini; Claudio, Luz; Robins, Thomas
Abstract Background In Malaysia, surveillance of fatal occupational injuries is fragmented. We therefore analyzed an alternative data source from Malaysia's Social Security organization, the Pertubuhan Keselamatan Sosial (PERKESO). Methods We conducted a secondary data analysis of the PERKESO database comprised of 7 million employees from 2002 to 2006. Results Overall, the average annual incidence was 9.2 fatal occupational injuries per 100, 000 workers. During the 5‐year period, there was a decrease in the absolute number of fatal injuries by 16% and the incidence by 34%. The transportation sector reported the highest incidence of fatal injuries (35.1/100, 000), followed by agriculture (30.5/100, 000) and construction (19.3/100, 000) sectors. Persons of Indian ethnicity were more likely to sustain fatal injuries compared to other ethnic groups. Conclusions Government and industry should develop rigorous strategies to detect hazards in the workplace, especially in sectors that continuously record high injury rates. Targeted interventions emphasizing worker empowerment coupled with systematic monitoring and evaluation is critical to ensure success in prevention and control measures. Am. J. Ind. Med. 56:65–76, 2013. © 2012 Wiley Periodicals, Inc.